Invariant NKT Cells Regulate the CD8 T Cell Response during Theiler's Virus Infection - Mars, Lennart T. (Public Library of Science, 2014)
Invariant NKT cells are innate lymphocytes with a broad tissue distribution. Here we demonstrate that iNKT cells reside in the central nervous system (CNS) in the absence of inflammation. Their presence in the CNS dramatically augments following inoculation of C57Bl/6 mice with the neurotropic Theiler's murine encephalomyelitis virus (TMEV). At the peak of inflammation the cellular infiltrate comprises 45 000 iNKT cells for 1 250 CD8 T cells specific for the immunodominant TMEV epitope. To study the interaction between these two T cell subsets, we infected both iNKT cell deficient Jα18(-/-) mice and iNKT cell enriched Vα14 transgenic mice with TMEV. The CD8 T cell response readily cleared TMEV infection in the iNKT cell deficient mice. However, in the iNKT cell enriched mice TMEV infection persisted and was associated with significant mortality. This was caused by the inhibition of the CD8 T cell response in the cervical lymph nodes and spleen after T cell priming. Taken together we demonstrate that iNKT cells reside in the CNS in the absence of inflammation and that their enrichment is associated with the inhibition of the anti-viral CD8 T cell response and an augmented mortality during acute encephalomyelitis.